Taxonomy, lectotypification and distribution of Andrographis stenophylla (Acanthaceae), a little known endemic species from southern India - Gnanasekaran, Gunadayalan; Murthy, Garimella Venkata Suryanarayana (Phytotaxa, 2014)
Andrographis stenophylla (Acanthaceae) is lectotypified and its taxonomy and distribution are discussed. The species is reported here as an addition to the flora of Andhra Pradesh and Kerala. Illustrations, photographs, a digital image of the selected lectotype and a distribution map are provided.